ANALISIS PENGARUH PENDAPATAN RUMAH TANGGA TERHADAP KONSUMSI DAGING DAN TELUR DI KECAMATAN SULUUN TARERAN KABUPATEN MINAHASA SELATAN - Weol, elvis F; Rorimpandey, B; Lenzun, G. D.; Endoh, E. K.M (Universitas Sam Ratulangi, 2014)
ABSTRACTHOUSEHOLD INCOMICANALYSIS AND ITS EFFECT ONMEAT AND EGG CONSUMPTIONAT SULUUN TARERAN DISTRICTOF SOUTH MINAHASAREGENCY. District of Suluun Tareranis the area located in the regency ofSouth Minahasa. The majority of SuluunTareran district communities areworking household farmers and minorityof this community are working as civilservants, private employees andbussinesman. The communityconsumption of meat and eggs dependslargely on the income earned. Thetendency of increased consumption ofmeat and eggs depends also on theincreased income of the community inthis regency. The higher the income thehigher also the deman tendency toconsume meat and egg. The problem ofthis study is that are the consumptions ofmeat and eggs in the District SuluunTareran influenced by householdincome? The purpose of this study wasto evaluate the amount of meat and eggconsumptions of the household and todetermine the effect of householdincome on the consumption of meat andeggs at the district of Suluun Tareran.This research has been conducted in thedistrict of Suluun Tareran involving thetotal sample of 74 respondent ofhouseholds. Data collection of thisresearch was conducted during 2 monthsusing survey method. The data waereanalysed using simple regressionanalysis to determine the effect ofincome on consumption of meat andeggs. The results showed that theaverage household income was Rp2,558,050 per month. Meat and eggconsumption have not reached the newtarget of 7.7 kg and 4.1 kg per capita peryear, respectively; to fulfill theappropriate food and nutrition workrecommended by widyakarya in 2004.The analysis showed that the householdincome significantly affect theconsumption of meat and eggs in theDistrict of Suluun TareranKeywords: Meat-egg consumption,Household Income,Suluun Tareran district